The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2001
DOI: 10.1046/j.1365-2125.2001.01306.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and knowledge of hospital pharmacists to adverse drug reaction reporting

Abstract: Aims To investigate the attitudes of UK hospital pharmacists towards, and their understanding, of adverse drug reaction (ADR) reporting. Methods A postal questionnaire survey of 600 randomly selected hospital pharmacists was conducted. Results The response rate was 53.7% (n=322). A total of 217 Yellow Cards had been submitted to the CSM/MCA by 78 (25.6%) of those responding. Half of those responding felt that ADR reporting should be compulsory and over threequarters felt it was a professional obligation. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
139
2
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(187 citation statements)
references
References 10 publications
41
139
2
5
Order By: Relevance
“…The initial draft of the survey questionnaire was developed using information from the literature about ADR reporting among healthcare professionals [19][20][21][22][23] as well as the findings of our previous qualitative study, which involved interviews with community pharmacists.…”
Section: Methodsmentioning
confidence: 99%
“…The initial draft of the survey questionnaire was developed using information from the literature about ADR reporting among healthcare professionals [19][20][21][22][23] as well as the findings of our previous qualitative study, which involved interviews with community pharmacists.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies of pharmacy education from the United States and United Kingdom, however, indicated issues with the extent, standardization, and effectiveness of instructions related to medication error and adverse drug event instruction. [3][4][5][6] This literature mainly focuses on explicit curriculum content and formal education related to patient safety in pharmacy. However, learning is not limited to formal content, environments, or mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…[21,22] Context learning has been proven to be more effective than sequential learning. [21][22][23] The present curriculum in pharmacology could be revised and appraised to incorporate more recent, relevant and practically applicable syllabus. Internship is meant to orient and equip the MBBS graduates to apply all the theoretical knowledge into actual clinical practice.…”
Section: Discussionmentioning
confidence: 99%